3D mechanical characterization of single cells and small organisms using acoustic manipulation and force microscopy - Nino F. Läubli (Nature Portfolio, 2021)
It is currently challenging to mechanically assess 3D specimens without manual handling. Here the authors combine a micro-force sensor and an acoustically controlled manipulation device to enable rotation of samples while assessing mechanical properties at the chosen region.